The world is my home : a memoir - Michener, James A. (James Albert), 1907-1997. (New York : Random House, 1992)
Literary legend James A. Michener was "a Renaissance man, adventurous, inquisitive, unpretentious and unassuming, with an encyclopedic mind and a generous heart" (The New York Times Book Review). In this exceptional memoir, the man himself tells the story of his remarkable life and describes the people, events, and ideas that shaped it. Moving backward and forward across time, he writes about the many strands of his experience: his passion for travel; his lifelong infatuation with literature, music, and painting; his adventures in politics; and the hard work, headaches, and rewards of the writing life. Here at last is the real James Michener: plainspoken, wise, and enormously sympathetic, a man who could truly say, "The world is my home."
Maps on lining papers.
Includes index.
Keywords: Michener, James A. -- 1907-1997.; Michener, James A. -- 1907-1997 -- Travel; Novelists, American -- 20th century -- Biography; Voyages and travels